2018
DOI: 10.1002/anie.201807998
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biosynthesis of β‐Alkyl Tryptophan Analogues

Abstract: Non-canonical amino acids (ncAAs) with dual stereocenters at the α and β positions are valuable precursors to natural products and therapeutics. Despite the potential applications of such bioactive β-branched ncAAs, their availability is limited due to the inefficiency of the multi-step methods used to prepare them. Here we report a stereoselective biocatalytic synthesis of β-branched tryptophan analogs using an engineered variant of Pyrococcus furiosus tryptophan synthase (PfTrpB), PfTrpB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 36 publications
0
63
0
Order By: Relevance
“…2 We evolved this enzyme to accept a variety of indole analogues and nitroalkanes with activated sp³-carbon atoms as nucleophiles ( Figure 1b). [3][4][5][6][7][8] However, these studies revealed limitations including chemo-and stereoselective control we would need to address in order to realize TrpB's broad potential as a biocatalyst for C-C bond formation. Previous biocatalytic reactions catalyzed by variants of TrpB [5][6]8 and proposed stereo-and chemo-selective reaction using engineered TrpB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 We evolved this enzyme to accept a variety of indole analogues and nitroalkanes with activated sp³-carbon atoms as nucleophiles ( Figure 1b). [3][4][5][6][7][8] However, these studies revealed limitations including chemo-and stereoselective control we would need to address in order to realize TrpB's broad potential as a biocatalyst for C-C bond formation. Previous biocatalytic reactions catalyzed by variants of TrpB [5][6]8 and proposed stereo-and chemo-selective reaction using engineered TrpB.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 TrpB is highly stereoselective and can retain the absolute configuration of the Cα of L-serine after product formation (Figure 1b). [3][4][5][6][7] However, the stereoselectivity at potential new stereogenic centers is unknown. Substrates with nucleophilic sp 3 -hybridized carbons have the ability to form a new quaternary carbon at the γ-position.…”
Section: Introductionmentioning
confidence: 99%
“…[66] Christina Boville and team engineered stand-alone PfTrpB 2B9 to accept β-branched Ser analogs with longer alkyl chains such as β-ethyl-and β-propylSer. [67] Bulkier alkyl chains at the β-position were thought to hinder nucleophilic attack, allowing the competing β-elimination to unproductively consume the electrophile. Initial activity with PfTrpB 2B9 on β-ethylSer and indole was too low for high-throughput screening, so the authors mutated an active-site residue presumed to clash sterically with the alkyl β-substitution.…”
Section: β-Branched Trpsmentioning
confidence: 99%
“…X-ray crystallography, measurement of the deamination rates and UVspectrophotometric evidence supported the hypothesis that evolution stabilized the closed conformation of the enzyme and generated a more persistent amino-acrylate that was less prone to unproductive β-elimination . [67]…”
Section: β-Branched Trpsmentioning
confidence: 99%
“…4.2.1.20) is a pyridoxal 5‐phosphate (PLP)‐dependent enzyme that catalyzes the synthesis of l ‐Trp from indole and l ‐Ser . Frances H. Arnold et al has reported that TrpS could react with myriad indole analogs to provide a direct biocatalytic route to l ‐Trp derivatives, a kind of l ‐ncAAs …”
Section: Introductionmentioning
confidence: 99%